A review of micro-mechanical cutting - Boswell, Brian; Islam, M.; Davies, I. (Springer, 2017)
The need for using alternative processes rather than electro-discharge machining (EDM) for micro-parts has allowed micro-manufacturing (also known as precision engineering) to become an important option due to its speed, economy, capability and extended range of materials. One main group of micro-manufacturing processes is that of micro-mechanical cutting with the focus of this review being micro-mechanical cutting processes that generate chips, namely, micro-turning, micro-milling and micro-drilling. Developments and future prospects for these micro-machining processes have been reviewed including micro-cutting configurations, cutting tools, tool coatings, cutting fluids, chip formation, surface finish, burr formation, modelling and industrial applications. The main advantages and disadvantages of these micro-manufacturing processes have been highlighted together with their future prospects.